Assessment of Macular Parameter Changes in Patients with Keratoconus Using Optical Coherence Tomography. (12th May 2015) - Sahebjada, Srujana; Amirul Islam, Fakir M.; Wickremasinghe, Sanj; Daniell, Mark; Baird, Paul N.
Abstract : Keratoconus is typically diagnosed through changes at the anterior ocular surface. However, we wished to assess if macular parameter changes might also occur in these patients. We assessed posterior changes through the use of optical coherence tomography and compared to a nonkeratoconus patient group. All subjects underwent clinical examination including macular thickness measurements. The generalized estimation equation model was used to estimate the means and compare the differences in various measurements between keratoconus and nonkeratoconus patients. A total of 129 keratoconus eyes of 67 cases and 174 nonkeratoconus eyes of 87 controls were analysed. Keratoconus individuals presented with a significantly greater mean retinal thickness in the central fovea, inner, and outer macula compared to the nonkeratoconus group (p < 0.05 ). In addition, individuals presenting with the early signs of keratoconus had significantly greater inner and outer macular volume compared to the nonkeratoconus group (p < 0.05 ). This study indicates the retina appears to thicken at the fovea and macula and had increased macular volume in keratoconus individuals compared to nonkeratoconus individuals. Thus we posit that structural retinal changes exist in keratoconus eyes that are additional to those typically seen in the anterior segment.